Cost-effectiveness of omalizumab in real world uncontrolled allergic asthma patients - A. Arrobas; M.P. Barbosa; S. Rabiais; B. Vandewalle; J. Félix (Pulmonology)
Objective To estimate the cost-effectiveness of omalizumab compared with standard of care in the treatment and control of severe persistent asthma, using the outcomes from the Portuguese subpopulation of the eXpeRience registry.Methods This was a pragmatic cost-effectiveness analysis based on real world data from the eXpeRience registry which recruited 62 patients with uncontrolled persistent allergic asthma from 20 participating centers in Portugal. Response to omalizumab treatment was measured prospectively up to 24 months by the physician’s Global Evaluation of Treatment Effectiveness (GETE). Retrospective data on patients’ clinical symptoms, asthma control, lung function, exacerbations, and healthcare utilization were available for up to 12 months before omalizumab initiation and served as the standard of care comparator. The number of exacerbations (severe and non-severe), the number of clinical episodes, the number of days absent from work and/or school, and GETE response to therapy were considered as effectiveness outcomes. Following a societal perspective, as cost indicators, both direct and indirect costs were considered. Direct costs relate to the cost of omalizumab, standard of care and clinical episodes (emergency room visits, hospitalizations, and unscheduled doctor visits). Indirect costs relate to the societal cost of work absenteeism. Unit costs for clinical episodes and drugs were taken from official sources within the Portuguese Health Authority. A univariate sensitivity analysis was performed.Results A rate of 1.5 exacerbations per patient-year was estimated following omalizumab treatment compared with 8.2 exacerbations per patient-year prior to omalizumab initiation, implying an 82.1% reduction in the incidence of exacerbations following omalizumab treatment relative to standard of care alone. A 54.1% reduction in GETE score was also observed in favor of omalizumab treatment. The mean cost per person-year was 3023є in the 12 months of standard of care prior to omalizumab and 16,111є in the period of treatment with omalizumab. The incremental cost-effectiveness ratios were 2244є/exacerbation avoided, and 1750є/unit decrease in GETE classification.Conclusion Our results demonstrate that adding omalizumab to the treatment of patients with uncontrolled severe persistent asthma reduces the number of exacerbations, improving overall treatment effectiveness at an acceptable cost from a societal perspective.